2017
DOI: 10.1111/jfb.13346
|View full text |Cite
|
Sign up to set email alerts
|

Global patterns and clines in the growth of common carp Cyprinus carpio

Abstract: This review provides a meta-analytical assessment of the global patterns and clines in the growth of Cyprinus carpio as measured by length-at-age (L ) or von Bertalanffy growth function (VBGF) parameters, mass-length relationship (W-L ) and condition factor, based on literature data. In total, 284 studies were retrieved spanning 91 years of research and carried out on 381 waterbodies-locations in 50 countries in all five continents. Although native C. carpio achieved larger (asymptotic) size relative to its no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 112 publications
(248 reference statements)
0
34
0
1
Order By: Relevance
“…Thus, the recommended (higher) CV threshold of 7.6% was retained given its metaanalytical foundation, although slight preference was given to the (lower and more conservative) APE threshold of 5%, which has been suggested as a ''reference point for many fishes of moderate longevity and reading complexity'' (Campana 2001, p. 224). In this respect, carp can effectively be categorised as a fish of moderate longevity (Vilizzi and Copp 2017), especially when compared to marine species, and the reading complexity of its ageing structures also match the above definition. Further, it is argued that the very strict 5% threshold value for the APE expected in some ageing laboratories (Morison et al 1998), whilst a solid indicator of the reproducibility of annulus counts, may by itself be biased by laboratory-specific protocols for annulus interpretation (hence, training of interpreters), which may differ from other laboratories (cf.…”
Section: Relative Utilitymentioning
confidence: 99%
See 4 more Smart Citations
“…Thus, the recommended (higher) CV threshold of 7.6% was retained given its metaanalytical foundation, although slight preference was given to the (lower and more conservative) APE threshold of 5%, which has been suggested as a ''reference point for many fishes of moderate longevity and reading complexity'' (Campana 2001, p. 224). In this respect, carp can effectively be categorised as a fish of moderate longevity (Vilizzi and Copp 2017), especially when compared to marine species, and the reading complexity of its ageing structures also match the above definition. Further, it is argued that the very strict 5% threshold value for the APE expected in some ageing laboratories (Morison et al 1998), whilst a solid indicator of the reproducibility of annulus counts, may by itself be biased by laboratory-specific protocols for annulus interpretation (hence, training of interpreters), which may differ from other laboratories (cf.…”
Section: Relative Utilitymentioning
confidence: 99%
“…With regard to longevity, estimated ages of 35 (Bajer and Sorensen 2010) and 23 years (Brown et al 2003) have been reported for carp based on otolith sections, although the oldest (mark-recapture validated) age using this method has been up to 14 years ). On the other hand, published otolith-based age-growth data on carp have so far been limited to the 1-19 years old range (Vilizzi and Copp 2017), indicating the need for further research (especially regarding validation) into this ageing method. At the same time, references to exceptionally old carp, albeit occasionally encountered in the literature, have been so far mostly anecdotal and based on individuals reared in captivity (e.g.…”
Section: Limited Longevitymentioning
confidence: 99%
See 3 more Smart Citations